+0  
 
+1
74
2
avatar+21 

 

NewuserEthan  Dec 13, 2017
Sort: 

2+0 Answers

 #1
avatar+81027 
+2

Mmmmmm...... looks lke the first step is incorrect.....

 

2x  -  4y  =  -6

3x  +  2y  = -1

 

6x - 12y  =  -18                ⇒  Multiplication Property of Equality

-6x - 4y  =     2

 

-16y  =  -16                    ⇒   Addition Property of Equality  (with simplification )

 

y  =  1                            ⇒  Division Property of Equality

 

2x  -  4(1)  =  - 6            ⇒  Substitution  

 

2x  -  4    =  - 6                ⇒  Simplification of previous step

 

2x    =   - 2                     ⇒  Addition Property of Equality

 

x  =  -1                            ⇒  Division Property of Equality

 

 

cool cool cool

CPhill  Dec 13, 2017
 #2
avatar+21 
+1

Thank You!!!

NewuserEthan  Dec 13, 2017

11 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details